Revision of the genus Narvesus Stål, 1859 (Hemiptera: Heteroptera: Reduviidae: Stenopodainae) and a new record for Argentina - Diez, Fernando (2014)
This is a revision of Narvesus Stål, a Neotropical genus with two species: Narvesus carolinensis Stål 1859 and Narvesus minor Barber 1930. Both known species are redescribed and illustrated, including data on male genitalia and new distri-butional records. We compared with the genus Diaditus Stål.